TRANSPARANSI INFORMASI PEMERINTAH DAERAH MELALUI WEBSITE: FAKTOR POLITIK ATAU KEUANGAN? - Sutaryo Sutaryo; Kurniasari Tri Amanu (Media Riset Akuntansi, Auditing & Informasi, 2020)
This research aims to examine the effect of political factors covering regent/mayor profile, political ideology and political competition level, and financial factors covering liquidity and regional independence on information transparency of local government in Indonesia. This study analyzes 309 Indonesian local government websites using multiple linear regression. The result shows that regent/mayor profile, political competition level and regional independence affect information transparency of local government. Meanwhile, political ideology and financial liquidity do not have significant effect. This result implies to local governments to improve their financial independence in order to encourage more complete information delivery. In addition, people should be more precise and careful on local government information, especially in a local government led by incumbent head and in low local political competition. Incumbent regional heads tend to deliver more information to defend their power while low local political competition leads to a tendency of lower information delivery.